A study of factors affecting customers’ demand towards loan provided by Sabah Credit Corporation / Siti Noorhazwanie Rosli - Rosli, Siti Noorhazwanie (2014)
The purpose of this study was to investigate the relationship of the selected independent variables : customer satisfaction, interest rate, service quality and demographic and dependent variable which is customer demand. In order to provide a guide of this study, three research objective were formulated. Data were collected from 100 respondents using the questionnaire. This study was conducted at sabah credit corporation, keningau Branch which is around keningau town, sabah and covers only by customers of Sabah Credit Corporation. Then, the results was analysed by using SPSS to discover the significant relationship between independent variable with the dependent variable. Through this research, it may help Sabah Credit Corporation know about their product perfomance and can get the new strategy for improve their service and product that they provide to their customer in future. Based on the findings, researcher can see most of the customer of sabah credit corporation actually from public sector. Besides, there also have determine the most factor that affecting customer demand towards loan provided by sabah credit corporation which is interest rate. From this findings, all the independent variables which is the factors also have a strong relationship with the customer demand towards loan that provided in sabah credit corporation.